2022
DOI: 10.3390/economies10120305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychological Variables on the Relationship between Customer Participation Behavior and Repurchase Intention: Customer Tolerance and Relationship Commitment

Abstract: The inseparability of the production and consumption of services without quality control makes it difficult to fully meet the diverse needs of customers. Despite a company’s continuous efforts to satisfy customers with perceived quality aimed at service success, if the customers’ expectations are not met, the customers will not be satisfied. This study empirically analyzed the effects of customer tolerance and relationship commitment as psychological variables on the relationship between customer participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Several studies state that relationship commitment is a parameter that is closely related to the formation of customer loyalty. In the study, it was found that customer participation behavior has a positive effect on relationship commitment (Kim & Hyun, 2022).…”
Section: Hypothesismentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies state that relationship commitment is a parameter that is closely related to the formation of customer loyalty. In the study, it was found that customer participation behavior has a positive effect on relationship commitment (Kim & Hyun, 2022).…”
Section: Hypothesismentioning
confidence: 93%
“…It was found that customer participation behavior has a positive effect on linking the two variables. Other studies place customer Kim & Hyun (2022), participation behavior as a variable that moderates brand image and customer engagement. It was found that customer participation has a moderate influence on both variables .…”
Section: Hypothesismentioning
confidence: 99%
“…Kim and Tang (2020) [5] highlight that these positive consumer-to-consumer interactions not only benefit firms but also promote the efficient flow of information. Lastly, tolerance behaviors are characterized by consumers' patience and leniency towards product or service shortcomings [37], often manifesting as forgiveness for corporate errors, opting against complaints, or allowing firms opportunities for correction. We propose theoretical hypotheses from the perspective of contrasting online and offline contexts, focusing on the differential impacts of CPV and CPCSR on the dimensions of CCB, including feedback, sharing, recommendation, and tolerance behaviors.…”
Section: Hypothesesmentioning
confidence: 99%